Coronal‐plane leg alignment in adolescence and the effects of activity: A full leg length MRI study. Issue 5 (5th October 2022) - Fernquest, Scott; Lloyd, Thomas; Pereira, Claudio; Gimpel, Mo; Birchall, Richard; Broomfield, John; Glyn‐Jones, Sion; Palmer, Antony
Abstract: The aim of this study was to explore the association between developing coronal‐plane leg alignment and activity levels during adolescence. We performed a cross‐sectional cohort study with individuals from soccer club academies and an age‐matched control population. Outcome measures were the hip knee angle (HKA), medial proximal tibial physeal angle (MPTPhyA), lateral distal femoral physeal angle (LDFPhyA) on full leg length magnetic reasonance imagine scans, and the physical activity questionnaire (PAQ) score. The cohort comprised 57 elite male soccer players, 34 male and 34 female controls aged 11−21 years. Mean HKA became more varus with age, with little change after 16 years or skeletal maturity. Skeletally mature elite male soccer players were significantly more varus than male controls with a HKA 2.28° less than male controls ( p < 0.001). Skeletally mature male controls had a HKA 1.34° less than female controls ( p < 0.001). A negative correlation existed between HKA and PAQ score (coefficient −0.24, p = 0.029). A positive correlation existed between HKA and MPTPhyA (coefficient 0.32, p = 0.008). In conclusion, high activity levels during adolescence are associated with the development of varus leg alignment. Mean HKA becomes more varus with age until skeletal maturity. The development of varus alignment may represent a physiological adaptation to load at the proximal tibial physis. Clinical Significance: A time period may exist for intervention before the development of varus leg alignment in young athletes, such as training load modification or proximal tibial morphology monitoring.